2022
DOI: 10.3390/ijms23105509
|View full text |Cite
|
Sign up to set email alerts
|

Potential Chemotherapeutic Effect of Selenium for Improved Canceration of Esophageal Cancer

Abstract: Esophageal squamous cell carcinoma is the most common type of esophageal cancer and accounts for 5% of malignant tumor deaths. Recent research suggests that chronic inflammation and DNA damage may drive the onset of esophageal squamous cell carcinoma, implying that lowering chronic inflammation and DNA damage compounds may provide chemo-prevention. According to epidemiological and experimental evidence, selenium is linked to a lower risk of several malignancies, including esophageal squamous cell carcinoma. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…Furthermore, it was shown that Se‐induced P53 activation may downregulate Bcl‐2 and upregulate Bax, which would induce Ehrlich cancer cells to undergo apoptosis (Ramakrishnan et al, 2009). These data agree with earlier research that Se promotes apoptosis in hematological malignancies, (Ehudin et al, 2022) leukemia and lymphoma cells (Wu et al, 2014) and esophageal cancer (Ahsan et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it was shown that Se‐induced P53 activation may downregulate Bcl‐2 and upregulate Bax, which would induce Ehrlich cancer cells to undergo apoptosis (Ramakrishnan et al, 2009). These data agree with earlier research that Se promotes apoptosis in hematological malignancies, (Ehudin et al, 2022) leukemia and lymphoma cells (Wu et al, 2014) and esophageal cancer (Ahsan et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it was shown that Se-induced P53 activation may downregulate Bcl-2 and upregulate Bax, which would induce Ehrlich cancer cells to undergo apoptosis (Ramakrishnan et al, 2009). These data agree with earlier research that Se promotes apoptosis in hematological malignancies, (Ehudin et al, 2022) leukemia and lymphoma cells (Wu et al, 2014) and esophageal cancer (Ahsan et al, 2022). It has been reported that, glutathione and Se interacted to form hydrogen selenide, or selenodiglutathione, which causes cytotoxicity in the form of DNA damage, ROS generation and cell death (Kim et al, 2021;Lipinski, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…In the years, special attention has been devoted to the potential usefulness of Se-containing compounds in the battle against cancer, acting as anticancer and chemopreventive agents, inducing antioxidant and pro-oxidant effects at low and high doses, respectively [ 48 , 49 ]. Inorganic compounds, especially selenite 3 , showed chemopreventive properties higher than the organic ones, despite their higher toxicity [ 50 ].…”
Section: Selenium-containing Compounds As Therapeutic Agentsmentioning
confidence: 99%
“…Numerous studies have shown selenium to be related to the risk of EC. It was reported that selenium could slow down the development of ESCC by decreasing the expression of Ki-67, inducing apoptosis, and lowering inflammation and oxidative DNA damage, thus exerting an important chemopreventive effect on ESCC by reducing high-grade dysplasia to low-grade dysplasia ( 47 , 48 ). Zhang et al ( 49 ) found that β-catenin/TCF pathway played a vital role in selenium induced-growth inhibition and apoptosis in ESCC cells ( 49 ).…”
Section: Seleniummentioning
confidence: 99%